Implementation of Land Procurement for Waqf Land Affected by the Solo-Ngawi Toll Road - Darmiko Irwansyah; Ahmad Sulchan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
The purpose of this study is to determine and analyze: 1). Implementation of land acquisition for Waqf land affected by the Solo-Ngawi toll road in Dibal Village, Ngemplak District, Boyolali Regency 2). Barriers and solutions to resolve the obstacles faced in the implementation of land acquisition for Waqf land affected by the Solo-Ngawi Toll road in Dibal Village, Ngemplak District, Boyolali Regency. The approach method in this research is juridical empirical, namely research that focuses on the behavior of individuals or communities in relation to law. The data used are primary and secondary data obtained through interviews and literature studies, while the data analysis method was carried out by qualitative descriptive analysis. The results of the research concluded that: 1) Implementation procurement of land to replace Waqf land affected by the Solo-Ngawi toll road in Dibal Village, Ngemplak District, Boyolal Regency, namely theplanning, preparation stages, implementation stages, submission of land exchange permits for Waqf to the Regional Office, stages of submitting results, submitting certificates of Waqf to BPN. 2).Obstacles faced in the implementation of land acquisition to replace the donated land affected by the Solo-Ngawi Toll road in Dibal Village, Ngemplak District, Boyolali Regency that is, the tardinesspermits, some of the Waqf land has disappeared or has died, it is difficult to find a replacement land that matches the value and area of the Waqf land affected by road construction. The solution to solve these obstacles, namely location data collection to speed up the issuance of permits, immediately look for a replacement Nadzhir, prioritizing deliberation and socialization. Deliberation to reach consensus is a way to get results that are fair to both parties.